IMPROVING THE PERFORMANCES OF A HIGH TC SUPERCONDUCTING CIRCULAR MICROSTRIP AN- TENNA WITH MULTILAYERED CONFIGURATION AND ANISOTROPIC DIELECTRICS - Benmeddour, Fadila; Bouttout, F (Université de M'sila , univ-msila.dz, 2010)
The moment method technique has been improved to in- vestigate the scattering properties of high Tc superconducting circular antennas with anisotropic substrate in multi-layered con¯guration. In this method, the electric ¯eld integral equation for a current element on a grounded dielectric slab of in¯nite extent was developed by basis functions involving Chebyshev polynomials. An improved analytical model is presented taking into account anisotropic substrate, super- conducting material for the circular patch and multilayered structure. To validate the theoretical results, an experimental study has been performed for a perfectly conducting circular patch on a single layer, with and without air gap. Good agreements were obtained between our theory and measurements. E®ects of temperature and thicknessof a superconducting ¯lm are also reported and discussed. The perfor- mances of high Tc superconducting circular antennas were improved by the use of uniaxial anisotropy substrate and multilayer con¯guration.
Keywords: IMPROVING THE PERFORMANCES OF A HIGH TC SUPERCONDUCTING CIRCULAR MICROSTRIP AN- TENNA WITH MULTILAYERED CONFIGURATION AND ANISOTROPIC DIELECTRICS , univ-msila.dz